2006
DOI: 10.1364/josaa.23.000468
|View full text |Cite
|
Sign up to set email alerts
|

Pseudodielectric functions of uniaxial materials in certain symmetry directions

Abstract: The pseudodielectric function is often used to represent ellipsometric data and corresponds to the actual dielectric functions of materials when there is no surface overlayer and the material is isotropic. If a uniaxial material is oriented such that the optic axis is in the plane of incidence or is perpendicular to the plane of incidence, then the cross-polarization terms are zero and appropriate pseudodielectric functions can be determined from the ellipsometry data. We calculate the pseudodielectric functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…We performed our study using a variable-angle spectroscopic ellipsometer as described elsewhere. [27][28][29][30][31] The technique of optical ellipsometry provides significant advantages over conventional reflection and transmittance methods in that it is self-normalizing and does not require reference measurements. The optical complex pseudodielectric function = Ј − iЉ is obtained directly without the Kramers-Krönig transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed our study using a variable-angle spectroscopic ellipsometer as described elsewhere. [27][28][29][30][31] The technique of optical ellipsometry provides significant advantages over conventional reflection and transmittance methods in that it is self-normalizing and does not require reference measurements. The optical complex pseudodielectric function = Ј − iЉ is obtained directly without the Kramers-Krönig transformation.…”
Section: Introductionmentioning
confidence: 99%
“…27 For isotropic crystals this function gives the value of the dielectric function of the material = ps if a surface roughness is taken into account properly. In the case of uniaxial crystals 28,29 the pseudodielectric function extracted from the measurements performed for two different orientations of the sample are a good approximation for the true dielectric function of the crystal. Thus, ps measured with p-polarized light for a crystal with the optical axis z lying in the plane of incidence gives the value of zz and, subsequently, of the extraordinary refractive and absorption indices.…”
Section: Introductionmentioning
confidence: 99%
“…12 Our data concern the intrinsic ε of a ZnGeAs 2 thin film grown epitaxially on GaAs. Since ZnGeAs 2 grows with its c axis normal to the surface and SE measurements are dominated by the component(s) of the ε tensor perpendicular to the c axis (here parallel to the measurement surface), 13,14 our data are a close approximation to the component ε a of ε. This is the component relevant for normal-incidence illumination.…”
Section: Introductionmentioning
confidence: 76%
“…͗ Ќ ͘ spectra obtained on an optically uniaxial crystal oriented with the optic axis perpendicular to the crystal surface are a close approximation to the ordinary component o of the dielectric tensor of the crystal, since the c-axis contribution is reduced approximately by 1 / ͗͘. 7,8 This approximation has been shown to be valid for single-crystal TiO 2 , which is highly anisotropic ͉͑⌬n͉Ϸ0.3͒ below the fundamental absorption edge. 8 Although a recent SE study 9 of wurtzite ZnO and GaN found a large discrepancy between ͗ Ќ ͘ and o in the transparent and excitonic-absorption regions, the discrepancy above the band gap is relatively small.…”
mentioning
confidence: 80%